2018
DOI: 10.1089/jmf.2017.0103
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Distribution to Essential Oils of Salmonella enterica Strains Involved in Animal and Public Health and Comparison of the Typhimurium and Enteritidis Serotypes

Abstract: To determine the distribution of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of essential oils (EOs) of cinnamon (Cinnamomum zeylanicum), clove (Eugenia caryophyllata), oregano (Origanum vulgare), common thyme (Thymus vulgaris), and red thyme (Thymus zygis) against Salmonella enterica, double serial dilutions of each EO were challenged with 85 Salmonella strains belonging to 23 serotypes of animal origin. The results showed the bactericidal character of the EOs teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
2
10
0
1
Order By: Relevance
“…patterns were found for both species investigated in this study. The concentrations found are in accordance to previous studies (Burt et al, 2016;Pei, Zhou, Ji, & Xu, 2009) and were lower than the ones found for others essential oils (oregano, thyme and clove) tested against the same species (Lara et al, 2016;Solarte et al, 2018). Furthermore, MIC and MBC values almost coincided (two-fold difference), which indicates that CNMA killing is generally bactericidal, a highly desirable mode of action to control microbial contamination (Ocampo et al, 2014).…”
Section: Antimicrobial Activity Of Cnma Towards Planktonic Cultures Osupporting
confidence: 90%
“…patterns were found for both species investigated in this study. The concentrations found are in accordance to previous studies (Burt et al, 2016;Pei, Zhou, Ji, & Xu, 2009) and were lower than the ones found for others essential oils (oregano, thyme and clove) tested against the same species (Lara et al, 2016;Solarte et al, 2018). Furthermore, MIC and MBC values almost coincided (two-fold difference), which indicates that CNMA killing is generally bactericidal, a highly desirable mode of action to control microbial contamination (Ocampo et al, 2014).…”
Section: Antimicrobial Activity Of Cnma Towards Planktonic Cultures Osupporting
confidence: 90%
“…The bark of cinnamon (Cinnamomum zeylanicum) significantly reduced S. enteritidis in cecal contents of infected chicken without affecting the total cecal endogenous population (Upadhyaya et al, 2014). These findings are supported by other scholars who revealed the higher antibacterial activity of essential oils of cinnamon (C. zeylanicum) against strains of Salmonella enterica after disrupting bacterial cell membrane (Vazirian et al, 2015;Solarte et al, 2018). Other species with essential oils effective in inhibiting Salmonella spp.…”
Section: Approaches and Challenges For Salmonella Controlmentioning
confidence: 52%
“…in chickens are clove (Eugenia caryophyllata), oregano (Origanum vulgare), common thyme (Thymus vulgaris), and red thyme (Thymus zygis). (Solarte et al, 2018).…”
Section: Approaches and Challenges For Salmonella Controlmentioning
confidence: 99%
“…The lack of the standardized method, the differences on the EOs composition (geographical origin, growth climatic and environmental conditions, part of the plant and the extraction method) and the variability of the botanical names, difficult the comparison of the results between different studies (29,32,35,42). In our study, EOs showed better antimicrobial activity than their main compounds, results that can be explained if consider that the molecules contained in very low proportion can also play an important role (32).…”
Section: Discussionmentioning
confidence: 66%
“…Essential oils are natural products with hydrophobic character and a complex chemical composition (13), which could be used for the treatment of diseases caused by resistant bacteria (27)(28)(29). In previous studies, we showed that cinnamon, oregano, thyme and their main compounds (cinnamaladehyde, carvacrol and thymol) could be used in combination with gentamicin and tetracycline for the control of resistant S. suis isolates from swine (19).…”
Section: Discussionmentioning
confidence: 99%